INTEGRATION OF COMPUTATIONAL THINKING ABILITIES IN RING THEORY LEARNING: ANALYSIS OF STUDENTS' ANSWER PROCESS - Nur Rahmi Rizqi; Yumira Simamora; Anjeli Malika Devani Tarigan; Kms. Muhammad Amin Fauzi; Edi Syahputra (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to analyze students' computational thinking skills in solving problems in ring theory material and to describe their thinking processes using computational thinking indicators.Methodology – This study engages Mathematics Education students undertaking the Ring Theory course in the even semester of the 2024/2025 academic year at a private university in Medan. This study used a dominant qualitative mixed-methods approach. The research instrument was a computational thinking ability test compiled based on four indicators: decomposition, pattern recognition, abstraction, and algorithmic thinking, as well as an interview guide to explore students' answer processes.Findings – The results showed that students' computational thinking skills were generally in the sufficient category (47%), with 28% in the poor category and 25% in the good category. Students were relatively capable of decomposing problems and recognizing patterns, but still experienced difficulties with abstraction and developing algorithmic solution steps. These findings indicate that integrating computational thinking into ring theory learning can help develop students' analytical and systematic thinking skills.Contribution – Implicitly, this study provides evidence of students' computational thinking profiles in ring theory learning and highlights the importance of integrating computational thinking to enhance analytical and systematic thinking skills in higher mathematics education.